Sexualization and Gamer Avatar Selection in League of Legends. Issue 2 (15th March 2017) - Bell, Christopher E.
ABSTRACT: To replicate and expand Reinhard's 2009 study of video game avatar selection in gamers, a survey was developed that asked 282 respondents to select between sets of video game characters. In each pair of characters, different levels of sexualization were displayed, and respondents had the choice between a more sexualized avatar or a less sexualized avatar. When presented with a choice between a subtly sexualized avatar and an overtly sexualized avatar, the overtly sexualized avatar was chosen. However, in nearly every case, when presented with a choice between a hypersexualized avatar and a less sexualized avatar, the less sexualized avatar was chosen. This seems to indicate that character sexualization reaches a point of diminishing returns for gamers and there is such a thing as too much sexualization in video games.